The utility of amniotic fluid pH and electrolytes for prediction of neonatal respiratory disorders. (17th January 2020) - Yılmaz Semerci, Seda; Yücel, Burak; Erbas, Ibrahim Mert; Gunkaya, Osman Samet; Talmac, Merve; Çetinkaya, Merih
Abstract: Background: Amniotic fluid (AF) is a complex structure with a changing content by gestation. Lower genomic expression of Na channels in airways was shown to be associated with respiratory distress syndrome (RDS). The aim of this study was to determine the possible role of amniotic fluid pH and electrolytes for prediction of neonatal respiratory morbidities. Methods: This was a prospective controlled cohort study. During C-section, 1 ml of AF was aspirated before incision of membranes. AF pH and electrolytes were analyzed by blood gas analyzer. Maternal and neonatal demographic features and clinical outcomes, respiratory morbidities were all recorded. Results: AF Na and K values were significantly higher in all infants with respiratory morbidities compared with those who did not develop respiratory findings. AF Na value was significantly higher in preterm neonates with RDS as well as in term neonates with transient tachypnea of the newborn (TTN). AF pH did not show any significant difference for prediction of respiratory morbidities in term and preterm infants. Conclusion: This is the first study that reported the value of AF Na and K levels for prediction of respiratory morbidities in term and preterm infants. However, further studies including larger number of infants are required to confirm the role of AF analysis to predict neonatal respiratory morbidities. Randomized controlled trial (RCT) number: NCT02813954.